Chinese workers in ethiopia caught between remaining and returning - Driessen, MLA (Pacific Affairs, 2021)
Ever since Beijing has sought to fuel domestic growth through Chinese-led development overseas—first under the aegis of Jiang Zemin’s Going Out Policy and more recently as part of Xi Jinping’s Belt and Road Initiative— thousands of Chinese have moved overseas for work. Africa has been one of the destinations of Chinese companies and their expatriate staff. Although we have learned a great deal about China’s mega-projects across the African continent, little is known about the certified engineers and experienced builders who carry them out. What brings them to Africa? And, more importantly, what makes them stay for years on end, even if they wish to return to China? In this article I zoom in on the lives of Chinese men employed in Ethiopia’s construction industry to show how three decades of domestic growth in China has pushed workers overseas, while jeopardizing their return. Workers’ lives are marked by double displacement. They are not only isolated from local African communities through a dormitory labour regime that controls their time and limits their mobility, but also, more importantly, they are displaced from social life in China. Domestic development has at once increased aspirations and made them harder to obtain, especially for men, who are expected to fulfill the promise of upward social mobility for themselves and their families. In order to realize aspirations and meet social expectations related to social reproduction, geographic mobility has become a necessity for men who cannot rely on family wealth or connections, forcing them into a state of suspension.